Internalizing Worship Discipline through Voluntary Fasting on Mondays and Thursdays: A Case Study at Surau Bansa Qur’anic Learning Center - Salmaa Zainabila; Fakhriyah Annisa Afroo (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study examined how voluntary fasting on Mondays and Thursdays was implemented at Surau Bansa Qur’anic Learning Center and how participating children, parents, and the teacher perceived its contribution to worship discipline. It also identified conditions supporting and constraining participation. A qualitative descriptive single-case design was employed from June to July 2026. Participants were one teacher, ten children aged 8–15 years, and five parents selected purposively because of their direct involvement in the program. Data were generated through non-participant observation, semi-structured interviews, and document analysis. Following the interactive model of qualitative analysis, data were condensed, displayed, coded, compared across sources, and interpreted through conclusion drawing and verification. Trustworthiness was supported through source, method, and time triangulation. The program connected WhatsApp reminders, parental assistance with the pre-dawn meal, afternoon Qur’anic learning, Thursday collective fast-breaking, congregational Maghrib and Isha prayers, teacher role-modeling, peer companionship, and rewards. Participants perceived development in punctuality, consistency in fasting and daily prayer, honesty, responsibility, and emotional regulation. These patterns were uneven and remained influenced by adult reminders, rewards, family routines, physical capacity, school schedules, missed pre-dawn meals, non-fasting peers, and exposure to the Free Nutritious Meals program. Rather than treating repeated fasting as automatic internalization, this study shows that worship discipline is negotiated across institutional, familial, peer, and school environments. The study proposes a distributed support model of religious habituation in which a non-formal Islamic institution, families, peers, and digital communication jointly sustain children’s worship practices. It offers context-sensitive guidance for designing voluntary, developmentally appropriate, and non-coercive religious programs. These findings clarify the distinction between observable compliance and personally endorsed commitment.